Comprehensive Mechanism of Gene Silencing and Its Role in Plant Growth and Development - El-Sappah, Ahmed H.; Yan, Kuan; Huang, Qiulan; Islam, Md. Monirul; Li, Quanzi; Wang, Yu; Khan, Muhammad Sarwar; Zhao, Xianming; Mir, Reyazul Rouf; Li, Jia; El-Tarabily, Khaled A.; Abbas, Manzar (Frontiers in Plant Science, 2021)
Gene silencing is a negative feedback mechanism that regulates gene expression to define cell fate and also regulates metabolism and gene expression throughout the life of an organism. In plants, gene silencing occurs via transcriptional gene silencing (TGS) and post-transcriptional gene silencing (PTGS). TGS obscures transcription via the methylation of 5′ untranslated region (5′UTR), whereas PTGS causes the methylation of a coding region to result in transcript degradation. In this review, we summarized the history and molecular mechanisms of gene silencing and underlined its specific role in plant growth and crop production.